Tetrel Bonding Interactions. Issue 1 (27th January 2016) - Bauzá, Antonio; Mooibroek, Tiddo J.; Frontera, Antonio
Abstract: Tetrel (Tr) bonding is first placed into perspective as a σ‐hole bonding interaction with atoms of the Tr family. An sp 3 R4 Tr unit has four σ‐holes with which a Lewis base can form a complex. We then highlight some inspiring crystal structures where Tr bonding is obvious, followed by an account of our own work. We have shown that Tr bonding is ubiquitous in the solid state and we have highlighted that Tr bonding with carbon is possible when C is placed in the appropriate chemical context. We hope that this account serves as an initial guide and source of inspiration for others wishing to exploit this vastly underexplored interaction. Abstract : Tetrel bonding interactions : Tetrel (Tr) bonding is first placed into perspective as a σ‐hole bonding interaction with atoms of the Tr family. An sp 3 R4 Tr unit has four σ‐holes with which a Lewis base can form a complex. We then highlight some inspiring crystal structures where Tr bonding is obvious, followed by an account of our own work. We hope that this account serves as an initial guide and source of inspiration for others wishing to exploit this vastly underexplored interaction.